Effect of γ-ethyl-γ-phenyl-butyrolactone (EFBL), anticonvulsant and hypnotic drug, on mouse brain catecholamine levels - Rasgado Lourdes A. Vega; Villanueva Iván; Díaz Fernando Vega (Acta Pharmaceutica)
γ-Ethyl-γ-phenyl-butyrolactone (EFBL) is a structural combination of the anticonvulsant γ-hydroxy-γ-ethyl-γ-phenylbutyramide (HEPB) and the hypnotic γ-butyrolactone (GBL), which inherits both properties. To clarify its mechanism of action, the effects of EFBL, GBL and HEPB on dopamine (DA) and noradrenaline (NA) brain levels were investigated. Influences of chlorpromazine, phenelzine and aminooxyacetic acid were also studied. EFBL increased DA in a dose-dependent manner, remaining enhanced by 80 % over a period of 24 h and augmented NA by 54 % one hour after treatment. HEPB increased DA and NA approximately 2-fold after the first hour. GBL raised DA and NA after three and 24 h, resp. EFBL reversed chlorpromazine effects but potentiated those of phenelzine on DA. Amino-oxyacetic modified neither DA nor NA brain levels, not even in the presence of EFBL. The anticonvulsant and hypnotic properties of EFBL are attributed to its effect on presynaptic dopaminergic receptors and its lasting effect on ethyl and phenyl radicals that hinder its degradation. The results support the role of DA and NA in regulating seizure activity in the brain and indicate that EFBL offers a potential treatment for refractory epilepsy without complementary drugs and Parkinson’s disease, without the drawbacks of oral therapies.